Burden of prediabetes, undiagnosed, and poorly or potentially sub-controlled diabetes: Lolland-Falster health study - Neda Esmailzadeh Bruun-Rasmussen; George Napolitano; Allan Kofoed-Enevoldsen; Stig Egil Bojesen; Christina Ellervik; Knud Rasmussen; Randi Jepsen; Elsebeth Lynge (BMC, 2020)
Abstract Background This study aimed to investigate prevalence and risk factors for prediabetes, undiagnosed diabetes mellitus, poorly and potentially sub-controlled diabetes in a rural-provincial general adult population in Denmark. Methods Using cross-sectional data from the Lolland-Falster Health Study, we examined a total of 10,895 individuals aged 20 years and above. Results Prevalence of prediabetes was 5.8% (men: 6.1%; women: 5.5%); of undiagnosed diabetes 0.8% (men: 1.0%; women: 0.5%); of poorly controlled diabetes 1.2% (men: 1.5%; women: 0.8%); and of potentially sub-controlled diabetes 2% (men: 3.0%; women: 1.3%). In total, 9.8% of all participants had a diabetes-related condition in need of intervention; men at a higher risk than women; RR 1.41 (95% CI 1.26-1.58); person aged + 60 years more than younger; RR 2.66 (95% CI 2.34-3.01); obese more than normal weight person, RR 4.51 (95% CI 3.79-5.38); smokers more than non-smokers, RR 1.38 (95% CI 1.19-1.62); persons with self-reported poor health perception more than those with good, RR 2.59 (95% CI 2.13-3.15); low leisure time physical activity more than those with high, RR 2.64 (95% CI 2.17-3.22); and persons with self-reported hypertension more than those without, RR 3.28 (95% CI 2.93-3.68). Conclusions In the Lolland-Falster Health Study, nearly 10% of participants had prediabetes, undiagnosed diabetes, poorly controlled, or potentially sub-controlled diabetes. The risk of these conditions was more than doubled in persons with self-reported poor health perception, self-reported hypertension, low leisure time physical activity, or measured obesity, and a large proportion of people with diabetes-related conditions in need of intervention can therefore be identified relatively easily.